Inflammation, Infectious Triggers, and Parkinson's Disease - Caggiu, Elisa; Arru, Giannina; Hosseini, Sepideh; Niegowska, Magdalena; Sechi, GianPietro; Zarbo, Ignazio Roberto; Sechi, Leonardo A. (Frontiers in Neurology, 2019)
Parkinson’s disease (PD) is a neurodegenerative syndrome that determines the progressive death of dopaminergic neurons of the substantia nigra pars compacta and a meaningful reduction in the concentration of dopamine in striatum. Studies on inflammogenic aspects of PD suggest that the disease results from an interaction between genetic and environmental factors while heterogeneity could always be seen in the clinical presentation of the illness. However, there is not enough knowledge on the etiology of the disease. The following review evaluates the possible impacts of inflammation and immune dysfunctions, specifically autoimmunity, in Parkinson's disease.